Lytic Bacteriophage PZL-Ah152 as Biocontrol Measures Against Lethal Aeromonas hydrophila Without Distorting Gut Microbiota - Feng, Chao; Jia, Kaixiang; Chi, Teng; Chen, Shuaimin; Yu, Huabo; Zhang, Liang; Haidar Abbas Raza, Sayed; Alshammari, Ahmed Mohajja; Liang, Shuang; Zhu, Zishan; Li, Tingxuan; Qi, Yanling; et al. (Frontiers in Microbiology, 2022)
Phage therapy is an alternative approach to overcome the problem of multidrug resistance in bacteria. In this study, a novel bacteriophage named PZL-Ah152, which infected Aeromonas hydrophila was isolated from sewage, and its biological characteristics and genome were studied. The genome contained 54 putative coding sequences and lacked known putative virulence factors, so it could be applied to phage therapy. Therefore, we performed a study to (i) investigate the efficacy of PZL-Ah152 in reducing the abundance of pathogenic A. hydrophila strain 152 in experimentally infected crucian carp, (ii) evaluate the safety of 12 consecutive days of intraperitoneal phage injection in crucian carp, and (iii) determine how bacteriophages impact the normal gut microbiota. The in vivo and in vitro results indicated that the phage could effectively eliminate A. hydrophila. Administering PZL-Ah152 (2×109 PFU) could effectively protect the fish (2×108 CFU/carp). Furthermore, 12-day consecutive injection of PZL-Ah152 did not cause significant adverse symptoms in the main organs of the treated animals. We also found that members of the genus Aeromonas could enter and colonize the gut. The phage PZL-Ah152 reduced the number of colonies of the genus Aeromonas. However, no significant changes were observed in α diversity and β diversity parameters, which suggested that the consumed phage had little effect on the gut microbiota. All the results illustrated that PZL-Ah152 could be a new therapeutic method for infections A. hydrophila.